Making homemade indicator and strips: a STEM + activity for acid-base chemistry with entrepreneurship applications. (6th October 2020) - Aydın-Günbatar, Sevgi
Abstract: Recent reforms have introduced integrated science, technology, engineering, and math education (STEM) that has highlighted an interdisciplinary approach to train students as better problem solvers. In addition to STEM disciplines, art, language, and other disciplines integration are also stressed (STEM+). In this paper, a STEM+ (STEM + art + entrepreneurship) activity was presented related to acid-base chemistry, specifically, pH indicator and strips designs. 13 junior pre-service chemistry teachers participated in the activity and produced indicator solutions from plant sources found easily at grocery stores and produced pH paper strips by the use of filter paper and coffee filters. After producing indicators and strips, participants were encouraged to marketing their products through product logo design and product advertisement. The activity is useful regarding learning acid-base chemistry, indicators and strips' properties, carrying out investigations, and designing solutions. The activity can also be easily applied to address high school physical science standards.